1980
DOI: 10.1073/pnas.77.4.2124
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage lambda vehicle for the direct cloning of Escherichia coli promoter DNA sequences: feedback regulation of the rplJL-rpoBC operon.

Abstract: ABSIRA4CA derivative of bacteriophage X, X 21, has been constructed and used for the cloning of Escherichia coli DNA fragments carrying promoters. Phaage X 21 lacks the lac promoter-operator and can accept DNA fragments up to 9.8 kilobases in size at a unique HindIII restriction endonuclease site adjacent to lacZ -Recombinant phage that carry promoters are readily identified by their expression of lacZ Lysogens of these phages in strains harboring a deletion of the chromosomal lac operon are capable of growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, examples were identified in Tenericutes, Thermotogae, Aquificae and Deinococcus-Thermus. The RNA is responsible for regulating rplJ and rplL in response to the L10(L12) 4 complex (44,45) (Figure 1). The minimal binding site identified using phylogenetic analyses and in vitro assays is characterized by a kink-turn motif followed by a bulged cytosine in the non-canonical stem (20).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, examples were identified in Tenericutes, Thermotogae, Aquificae and Deinococcus-Thermus. The RNA is responsible for regulating rplJ and rplL in response to the L10(L12) 4 complex (44,45) (Figure 1). The minimal binding site identified using phylogenetic analyses and in vitro assays is characterized by a kink-turn motif followed by a bulged cytosine in the non-canonical stem (20).…”
Section: Resultsmentioning
confidence: 99%
“…atn + rpoBp. In addition to an attenuator, several experiments have suggested that a weak promoter is also located in the rpIL-rpoB intercistronic region (2,5,20,28). Thus, to determine whether the rpoBC genes are transcribed at a significant level from a promoter in this region, the DNA encompassed by the EcoRI sites in rpIL and rpoB was joined to lacZ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…380 nucleotides upstream of rpli (37,39). However, when segments of the operon were analyzed either by cloning them upstream of lacZ on a plasmid (2,5,21) or transducing phage (20) or directly by cloning onto a lambda transducing phage and examining the synthesis of the gene products in the UVirradiated cell system (28), it was suggested that there were internal promoters preceding rplL and rpoB. Most of these experiments indicated that these promoters were relatively weak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the inhibition offMet-Val synthesis by RNA polymerase with Arifdl8 DNA as template is somewhat greater than that with pNF1337 as template, a similar overall effect of RNA polymerase is observed. Maximum synthesis of fMet-Val is seen with 2-5 jig ofRNA polymerase and significant.inhibition is seen with [10][11][12][13][14][15] ,ug of RNA polymerase. As a control for these experiments, expression of the L12 gene was determined by measuring the formation of fMet-Ser (using Ser-tRNASer) under similar conditions.…”
Section: Resultsmentioning
confidence: 99%